Implications of Philosophical Thinking on the Practice of Inclusive Education in a Social Context - Youke Singal (PT Publikasiku Academic Solution, 2024)
Inclusive education refers to an education system that allows all children without exception to learn together in one classroom. Inclusive education is based on philosophical thinking that emphasizes equality, social justice, and respect for diversity. The purpose of this study is to analyze the implications of philosophical thinking for the practice of inclusive education in a social context. This study applies a qualitative research approach, using a literature study as a data collection technique. The collected data were analyzed through three stages, namely data reduction, presenting data, and drawing conclusions. The results show that philosophical thoughts on equality, social justice, and respect for diversity form the basis for inclusive education practices. Philosophical thinking has significant implications for inclusive education practices. Inclusive schools that are based on strong philosophical thinking have greater potential to achieve their goal of providing quality and equitable education for all children